Influence of stacking sequence on the mechanical properties of 3D E-glass/bamboo non-woven hybrid epoxy composites. (2021) - Nayak, Suhas Yeshwant; Shenoy, B. Satish; Sultan, Mohamed Thariq Bin Hameed; Kini, Chandrakant R.; Shenoy, K. Rajath; Acharya, Anarghya; Jaideep, J.P.
Abstract: Hybridization of composites is one of the many ways to optimize cost, manufacturing process and strength required for a particular application. This demands a need for knowledge about the best possible ways to deal with the dissimilar materials in the composite system. Very little light has been shed about the stacking sequence implemented while dealing with non-woven natural fiber mats and 3D woven glass fiber fabric as reinforcement and effects of different models on the strength of composite – which has been dealt very vividly in this research work. Two types of hybrid stacking sequence were implemented using non-woven bamboo fiber mat and 3D E-glass fiber fabric, namely H1, which has two bamboo mats at the centre with a glass fabric on either side as extreme layers, and H2, which has 3 glass fabric and 2 bamboo mat placed stacked alternatively with glass fabric being as extreme layers on either side again. For comparative purposes, 4 layers each of E-glass fabric and bamboo mat composites were also made. Tensile, flexural and ILSS tests were conducted on all four of these samples and results showed that lying between the consistent superior strength displayed by pure glass composite and inferior strength of pure bamboo composite, the H1 sample stacking sequence performed better than the H2 sample. The major reason for the failure of the hybrid composites was observed to be due to delamination at dissimilar laminae boundary which were more in H2 samples than H1 composite. Scanning Electron Microscopy was employed to understand the modes of failure.